2016
DOI: 10.5713/ajas.15.1050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Replacing Pork Back Fat with Canola and Flaxseed Oils on Physicochemical Properties of Emulsion Sausages from Spent Layer Meat

Abstract: The objective of this study was to investigate the effects of canola and flaxseed oils on the physicochemical properties and sensory quality of emulsion-type sausage made from spent layer meat. Three types of sausage were manufactured with different fat sources: 20% pork back fat (CON), 20% canola oil (CA) and 20% flaxseed oil (FL). The pH value of the CA was significantly higher than the others (p<0.05). The highest water holding capacity was also presented for CA; in other words, CA demonstrated a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 30 publications
7
21
0
2
Order By: Relevance
“…Many researchers have reported that fat plays a major role in meat or meat analogue quality such as juiciness, tenderness, mouthfeel, and flavor release of the product [5][6][7][8][9]. However, vegetable oils differ considerably in their physicochemical properties from animal fats, and this can therefore negatively affect juiciness and texture parameters [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that fat plays a major role in meat or meat analogue quality such as juiciness, tenderness, mouthfeel, and flavor release of the product [5][6][7][8][9]. However, vegetable oils differ considerably in their physicochemical properties from animal fats, and this can therefore negatively affect juiciness and texture parameters [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The meat of OHLs is difficult to sell directly to the consumer because of its low quality [10]. In recent years, studies have been undertaken to process the meat from OLH into meat products to promote consumption and provide added value [11][12][13]. Therefore, the aim of this study was to better understand and provide scientific information regarding the utilization of different chicken breeds to manufacture retorted Samgyetang, which is expected to be used as basic information for the diversification of Samgyetang products.…”
Section: Introductionmentioning
confidence: 99%
“…Restructured meat products such as patties and sausages are an important part of both the meat product and fast-food industries. Recently, the demand for healthier meat and processed meat products has increased (Ahn et al, 2019;Baek et al, 2016;Hoffman and Mellett, 2003). An excessive intake of animal fat can cause cardiovascular disease, high cholesterol, obesity, and chronic diseases (Hur et al, 2008;Serdaroğlu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%